Clinical and Pathological Characteristics of Hyaline-Vascular Type Unicentric Castleman Disease: A 20-Year Retrospective Analysis - Midori Filiz Nishimura (MDPI AG, 2021)
The first case of hyaline vascular type of unicentric Castleman disease (HV-UCD) was reported more than six decades ago. Since patients with HV-UCD are often asymptomatic and this condition is generally discovered incidentally on imaging tests, most of the previous reports were of mediastinal origin detected by chest radiography. In recent years, improved access to imaging modalities has provided new insights in the diagnosis of this condition. In this study, we reviewed the detailed clinical and pathological findings of 38 HV-UCD cases (20 males and 18 females, mean age: 42.8 years). The most common site involved was the abdominal cavity (34.2%), followed by mediastinum (23.7%) and retroperitoneum (15.8%). In the abdominal cavity, mesenteric origin was the most common. The mean size of masses was 4.8 cm. Pathologically, thick hyalinized collagen fibers surrounding large blood vessels and calcification were observed (81.6% and 23.7%, respectively). Multinucleated giant cells resembling Warthin–Finkeldey cell were also observed in occasional cases (23.7%). This is a unique paper that summarizes detailed clinical and pathological findings of a large series of a rare disease. The clinical information presented in this paper is more plausible than previous views and is useful for accurate diagnosis and understanding of the disease.